Formulation of Shampoo from Rice Bran Extract (Oryza sativa) and Essential Oil Pomelo Peel (Citrus maxima) - Hadi, Ismanurrahman; Silviyani, Amerta; Ulfah, Mariam (Universitas Muhammadiyah Yogyakarta, 2024)
Rice bran (Oryza sativa) is a by-product of rice processing that contains bioactive terpenoid compounds such as oryzanol. This compound has many pharmacological effects such as antioxidant, anti-fungal, anti-bacterial, etc. On the other hand, the essential oil of pomelo peel (Citrus maxima) has a refreshing aroma and also contains a variety of phytochemicals that are efficacious as antioxidants. This study aims to identify optimal formulations of shampoo with a combination of acetone extract from rice bran and essential oil of pomelo peel. Rice bran was extracted using acetone solvent, while essential oil from pomelo peel was obtained by distillation. Phytochemical screening of acetone extract showed the presence of terpenoids, flavonoids, alkaloids, tannins, and saponins. The extracts and essential oil were formulated into shampoo into 4 groups (FI, FII, FIII, FIV), which respectively contained 0%, 10%, 15%, and 20% extract. The results showed the evaluation of the best physical shampoo in Formula III because volunteers preferred Formula III and its better foam stability. Based on these results, it can be concluded that the acetone extract of rice bran and the essential oil of pomelo peel could be formulated into good shampoo.